Structural investigations of La0.6Sr0.4FeO3−δ under reducing conditions: kinetic and thermodynamic limitations for phase transformations and iron exsolution phenomena. Issue 6 (15th January 2018) - Götsch, Thomas; Schlicker, Lukas; Bekheet, Maged F.; Doran, Andrew; Grünbacher, Matthias; Praty, Corsin; Tada, Mizuki; Matsui, Hirosuke; Ishiguro, Nozomu; Gurlo, Aleksander; Klötzer, Bernhard; Penner, Simon
Abstract : A dependence of structural transformation and iron exsolution on chemical environment and reducing conditions is proven for the perovskite La0.6 Sr0.4 FeO3− δ . Abstract : The crystal structure changes and iron exsolution behavior of a series of oxygen-deficient lanthanum strontium ferrite (La0.6 Sr0.4 FeO3− δ, LSF) samples under various inert and reducing conditions up to a maximum temperature of 873 K have been investigated to understand the role of oxygen and iron deficiencies in both processes. Iron exsolution occurs in reductive environments at higher temperatures, leading to the formation of Fe rods or particles at the surface. Utilizing multiple ex situ and in situ methods ( in situ X-ray diffraction (XRD), in situ thermogravimetric analysis (TGA), and scanning X-ray absorption near-edge spectroscopy (XANES)), the thermodynamic and kinetic limitations are accordingly assessed. Prior to the iron exsolution, the perovskite undergoes a nonlinear shift of the diffraction peaks to smaller 2 θ angles, which can be attributed to a rhombohedral-to-cubic ( R 3̄ c to Pm 3̄ m ) structural transition. In reducing atmospheres, the cubic structure is stabilized upon cooling to room temperature, whereas the transition is suppressed under oxidizing conditions. This suggests that an accumulation of oxygen vacancies in the lattice stabilize the cubic phase. The exsolution itself is shown to exhibit a diffusion-limited Avrami-like behavior, where the transport of iron to the Fe-depleted surface-near region is the rate-limiting step.